The Etiological Diagnosis of Diabetes: Still a Challenge for the Clinician - Danièle Dubois-Laforgue; José Timsit (Endocrines, 2023)
The etiological diagnosis of diabetes conveys many practical consequences for the care of patients, and often of their families. However, a wide heterogeneity in the phenotypes of all diabetes subtypes, including Type 1 diabetes, Type 2 diabetes, and monogenic diabetes, has been reported and contributes to frequent misdiagnoses. The recently revised WHO classification of diabetes mellitus includes two new classes, namely “hybrid forms” and “unclassified diabetes”, which also reflect the difficulties of this etiological diagnosis. During the last years, many studies aiming at identifying homogenous subgroups on refined phenotypes have been reported. Ultimately, such subtyping may improve the diagnosis, prognosis, and treatment of patients on a pathophysiological basis. Here, we discuss the concepts of typical vs. atypical diabetes in the context of autoimmune Type 1 diabetes, Type 2 diabetes, and its monogenic forms. We discuss the contributions of clinical markers, biological tests, particularly islet cell auto-antibodies, and genetics to improving accurate diagnoses. These data support a systematic evaluation of all newly diagnosed diabetes cases.